(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
The risk of development (or disaster) depends on the nature of the development itself and the potential disaster in the development area. However, the risk of disasters is a matter of perception. It depends on how an individual or group of individuals see or assess the characteristics of a phenomenon. Even it is subjective; it is vital to understand what risks people consider to be acceptable, especially the local players involved in the development works. Therefore, this paper presents how the local players perceive disaster risk in underground utility development. These local players were the authorities at the federal and state level, industry players, and academicians. Series of focus group discussions were conducted for data collection purposes, and the data was analyzed narratively. One aspect is the perception of disaster risk occurrence; either the disaster affects the development or otherwise. In turn, this evidence-based information could be one of the essential feeders to policymakers and disaster managers on what disaster risk reduction programmes have a better chance of being accepted by the local players. The success of this kind of programme is essential for sustainable underground utility functions for the future.